Pleuroparenchymal Lung Disease Secondary to Nonoccupational Exposure to Vermiculite - Fahad Al-Ghimlas; Victor Hoffstein (Canadian Respiratory Journal)
An unusual case of pleuroparenchymal lung disease caused by the inhalation of vermiculite dust, presumably containing asbestos fibers is described. The uniqueness of the case lies in the very indirect nature of exposure – the wife of a factory owner, rather than a worker exposed to asbestos, whose factory manufactured vermiculite. The present case illustrates the importance of taking careful occupational histories of all household members when presented with a patient whose chest radiograph exhibits features consistent with asbestos exposure.